2017
DOI: 10.1002/jbmr.3321
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Advanced Glycation End Products Have Sex- and Age-Dependent Effects on Vertebral Bone Microstructure and Mechanical Function in Mice

Abstract: Back pain is a leading cause of global disability that can arise from vertebral fracture and osteoporosis. Although poor general health and obesity are among the strongest risk factors for back pain, there is remarkably little known about how diet influences spinal diseases. Advanced glycation end-products (AGEs) are implicated in increased fracture risk, yet no studies investigated how dietary AGEs affect spinal health. We tested the hypothesis that high dietary AGE ingestion will diminish vertebral structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 60 publications
4
37
2
Order By: Relevance
“…Causes for the sex-dependent effects of dietary AGEs warrant future investigation, especially because estrogen is known to regulate cell metabolism (Mauvais-Jarvis et al, 2013) and to influence the receptor for AGEs (Tanaka et al, 2000). We previously have shown that dietary AGEs affect bone mechanical properties mostly in young female mice (Illien-Junger et al, 2018), which further emphasizes the importance of assessing male and females separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Causes for the sex-dependent effects of dietary AGEs warrant future investigation, especially because estrogen is known to regulate cell metabolism (Mauvais-Jarvis et al, 2013) and to influence the receptor for AGEs (Tanaka et al, 2000). We previously have shown that dietary AGEs affect bone mechanical properties mostly in young female mice (Illien-Junger et al, 2018), which further emphasizes the importance of assessing male and females separately.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed in ageing pre-diabetic mice, that chronic ingestion of diets enriched with the specific AGE precursor (methylglyoxal) accelerated agerelated vertebral bone loss and induced AGE accumulation within the endplate (Illien-Junger et al, 2015). When further investigated, ingestion of dietary AGEs induced sex dependent bone loss with inferior biomechanical properties in young (6m) female mice (Illien-Junger et al, 2018). These studies provided the first evidence that dietary AGEs had a direct effect on vertebral structure and function, and also showed that this effect was sex-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…A study in young female mice fed with a high-AGE diet for 6 months showed deterioration of vertebral microarchitecture and a decrease in fracture resistance. (47) in vitro glycation studies, on biopsy specimens from both living donors and cadavers, showed that cancellous bone is more susceptible to non-enzymatic glycation than cortical bone. (48,49) The more efficient glycation of bone matrix proteins in cancellous bone is due to higher surface area to volume ratio, which could have facilitated better accessibility of the sugars to the matrix proteins.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 99%
“…After bone mass reaches a peak in the third or fourth decade of life, vertebral bone mass and density decrease with aging for both females and males [43]. Moreover, AGEs accumulation occurs in the bone with aging, increasing by 4 to10 fold at the age, of 50 years old [44]. [45], [46].…”
Section: Discussionmentioning
confidence: 99%